METHODS OF TEACHING STUDENTS THE ABILITY TO APPLY KNOWLEDGE COMPREHENSIVELY TO SOLVING COMPLIANCE PROBLEMS - Jonzakov, Azizjon (Физико-технологического образование, 2021)
This paper examines the problems arising for teachers in the formation of students’ complex application of knowledge from various sections of physics courses and other academic disciplines. Also, a methodology for the formation of the ability to solve educational and cognitive complex problems is proposed.